2016
DOI: 10.1002/ijc.30546
|View full text |Cite
|
Sign up to set email alerts
|

Potential of long non‐coding RNAs in cancer patients: From biomarkers to therapeutic targets

Abstract: Because of high specificity and easy detection in the tissues, serum, plasma, urine and saliva, interest in exploring the potential of long non-coding RNAs (lncRNAs) in cancer patients continues to increase. LncRNAs have shown potential as a biomarker in the diagnosis and prognosis of bladder cancer, prostate cancer, gastric cancer, pancreatic cancer, breast cancer and many other cancer types. Some lncRNAs have also been used as adjunct to improve the specificity and sensitivity of existing biomarkers. The mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
260
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(275 citation statements)
references
References 148 publications
1
260
1
Order By: Relevance
“…Triple‐negative breast cancer is a heterogeneous disease at the cellular, molecular, and clinical levels (Lehmann et al ., ). Long non‐coding RNA have recently emerged as important players implicated in relevant biological processes (Martin and Chang, ) as well as potential cancer biomarkers or therapeutic targets (Arun et al ., ; Chandra Gupta and Nandan Tripathi, ; Prabhakar et al ., ; Wan et al ., ; Wu and Du, ). In the present study, we classified TNBC using mRNA expression profiles (Chen et al ., ) and identified several lncRNA expressed in specific tumor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Triple‐negative breast cancer is a heterogeneous disease at the cellular, molecular, and clinical levels (Lehmann et al ., ). Long non‐coding RNA have recently emerged as important players implicated in relevant biological processes (Martin and Chang, ) as well as potential cancer biomarkers or therapeutic targets (Arun et al ., ; Chandra Gupta and Nandan Tripathi, ; Prabhakar et al ., ; Wan et al ., ; Wu and Du, ). In the present study, we classified TNBC using mRNA expression profiles (Chen et al ., ) and identified several lncRNA expressed in specific tumor subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Another method is based on the usage of antisense oligonucleotides (ASOs) that are either short single-stranded RNAs or DNAs antisense to their target lncRNA [91]. Moreover, the use of small molecules can, for example, inhibit the interaction of HOTAIR with LSD1 and PRC2 [92,93]. The therapeutic usage of H19-regulated double-stranded DNA plasmid BC-819 has already been successfully tested in patients with bladder cancer [94].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high‐throughput sequencing technology, it has been revealed that the non‐coding RNA (ncRNA) accounted for more than 95% of the human genome, and the complex interaction between the protein encoding RNA and functional ncRNA played an important role in the occurrence and development of HCC . Long ncRNA (lncRNA), as one of the important components of ncRNA, has been paid more and more attention to, which has been shown to be involved in epigenetic, gene transcription, post transcriptional regulation, and translation and has potential as a marker for early disease diagnosis …”
Section: Introductionmentioning
confidence: 99%